Environment, Genesis: Exploring the Spectrum of Environmentalism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The environmental issues are of prime importance and significance, as the absence of their solutions, the impact is horrifying. Unless environmental issues are addressed to in the right earnestness, the future generations would find earth not worth living. If the present generation does not rise up to the occasion and take timely remedial and precautionarycorrective measures at this endangered and critical juncture, the very survival of the mankind would be at stake. The Human race needs to understand the importance and significance of environment in the present day world, environment encompasses the things around the human being i.e. air, water, forest, trees including animal being, birds etc the need of the hour is conserve and improve the environment in a holistic manner . Here we shall make an attempt to find out the specific meanings attached to the concept of environmentalism. Some say it should include totality of all components surrounding man. That means it includes all living thingsspecies, the air, water and soul which is their habitat.While for others, it means a little more than resource conservationism that see nature as a feeder and if exploited sensibly then such conserved environment will act as catalyst of growth . There are on the other hand are environmental protectionists who are mainly concerned with public health, thus gave emphasis on atmospheric and water pollution, the need for public park and public education and awakening. There are still the others known as the mainstream greens whose emphasis is on renewable energy on recycling of waste into raw materials and on meeting real human needs. There are yet “Deeper Green” thinkers who believe that mindless rampant industrialization devoid of preserving the environment would result in nature to show its devastating color. The analysis of the spectrum of environment would be incomplete if all the stakeholders who are supposed to conserve preserve environment do not come on same platform i.e. environmentalist, zoologist etc whose activities are intradependent and shall have to approach the problem confronted by living beings with an integral approach.